Efficient numerical calculation of frequency-domain matching method based on an analytical control surface. (August 2022) - Deng, Baoli; Shan, Penghao; Liu, Ruixiang; Wang, Zhe; Li, Hui
Highlights: The matching method based on an analytical control surface in the frequency-domain. The integration of the forward speed Green function are performed analytically. An efficient scheme is developed by combining several computational techniques. Good agreement is achieved through comparisons with known benchmark data. Abstract: The matching method based on an analytical control surface has been developed to predict wave-induced motions and loads of ships with forward speed. Taking advantage of several computational techniques, this study proposes an efficient scheme for the numerical calculation of this novel method. Different from the conventional domain decomposition strategy, the control surface is analytical, and the physical quantities on it are expanded into the Fourier-Laguerre series. Therefore, the integration over the control surface associated with the forward speed Green function is performed analytically, avoiding the convergence problem caused by the singular and oscillatory behaviors of the forward speed Green function. Because the introduction of the analytical control surface may cause large computational burdens, an efficient scheme is developed by combing threaded parallelism, Chebyshev series approximation, and shared B-spline data. The excellent agreement between numerical results and experimental measurements shows that the present numerical method is reliable and practical in several applications. Furthermore, the numerical validation reveals that the present numerical scheme is affordable on the standard computing platform.